Energy Efficiency and Productivity Enhancement of Microbial Electrosynthesis of Acetate - LaBelle, Edward V.; May, Harold D. (Frontiers in Microbiology, 2017)
It was hypothesized that a lack of acetogenic biomass (biocatalyst) at the cathode of a microbial electrosynthesis system, due to electron and nutrient limitations, has prevented further improvement in acetate productivity and efficiency. In order to increase the biomass at the cathode and thereby performance, a bioelectrochemical system with this acetogenic community was operated under galvanostatic control and continuous media flow through a reticulated vitreous carbon (RVC) foam cathode. The combination of galvanostatic control and the high surface area cathode reduced the electron limitation and the continuous flow overcame the nutrient limitation while avoiding the accumulation of products and potential inhibitors. These conditions were set with the intention of operating the biocathode through the production of H2. Biofilm growth occurred on and within the unmodified RVC foam regardless of vigorous H2 generation on the cathode surface. A maximum volumetric rate or space time yield for acetate production of 0.78 g/Lcatholyte/hour was achieved with 8 A/Lcatholyte (83.3 A/m2projected surface area of cathode) supplied to the continuous flow/culture bioelectrochemical reactors. The total Coulombic efficiency in H2 and acetate ranged from approximately 80% to 100%, with a maximum of 35% in acetate. The overall energy efficiency ranged from approximately 35% to 42% with a maximum to acetate of 12%.